Evaluation of Fuel Economy of Tractor - Loader with Mechanical Stepless Transmission - A.A. Blagonravov; A.V. Yurkevitch (Механика машин, механизмов и материалов, 2009)
Authors offer some information on technical solutions that increase the reliability and availability of mechanical stepless transmission, where rotation is converted into corner fluctuations of several intermediate links, and then back into the rotation by mechanical rectifiers connected with the supporting shaft through torsion shaft. The regulation of the amplitude of fluctuations makes it possible to load the engine with the minimum specific fuel expense. We have estimated the fuel economy rating in the application of such transmission instead of hydro-mechanical one on tractor-loader. The fuel saving was more than 26 %.